Transformasi Bisnis dengan Penerapan Kecerdasan Buatan (AI) pada Sistem Informasi dan Teknologi Digital: Tren Utama Tahun 2023 (Yayasan Kawanad, 2023)
This study examines business transformation through the application of artificial intelligence (AI) on information systems and digital technology, with a focus on the main trends that occurred in 2023. Using a mixed method, this study involved quantitative surveys and qualitative interviews to obtain data on comprehensive from 120 companies in various industrial sectors. The results showed that 85% of companies had integrated AI in their business functions, with supply chain management, production management, marketing, and customer service as the main application area. The application of AI is proven to increase operational efficiency, reduce costs, and accelerate decision making. However, challenges such as high initial investment and integration with existing systems are still obstacles. This research highlights the importance of a holistic approach which includes technology and human aspects of implementing AI. In conclusion, AI is the main driver of business transformation, and companies that are able to overcome challenges and utilize their potential effectively will get a significant competitive advantage. Further research is needed to explore the long-term impact and ethical issues related to the use of AI.